Teachers knowledge and awareness of attention deficit hyperactivity disorders (ADHD) among primary school pupils with learning disabilities (2009)
This study examined teachers’ knowledge and awareness of attention deficit hyperactivity disorders among pupils with learning disabilities in Ibadan north local government, Oyo State of Nigeria. Three hypotheses were formulated based on the variables. The study adopted an ex post- facto research method whereby the questionnaire was used to elicit responses from ninety primary school teachers that were selected through systematic sampling technique. The t-test and chi- square statistical methods were utilised in testing the three null hypotheses generated for the study at 0.05 level of significance. Findings of the study revealed that: there was no significant difference between male and female teachers' knowledge and awareness of attention deficit hyperactivity disorder. This implies that both male and female teachers used for this study had no knowledge of ADHD. Similarly both young and old teachers had no knowledge of ADHD. There is equally no significant difference between the private and public primary school pupils in their manifestation of ADHD the researchers used for the research.